Technological Innovation in the Pharmaceutical Industry: The Use of Organizational Control in Managing Research and Development - Cardinal, Laura B. (Organization Science, 2001)
The literature on the management of R&D professionals strongly advocates managing R&D projects on a project-by-project basis. This literature suggests that projects should be managed differently depending upon project characteristics such as risk, ambiguity, and nonroutineness. While the primary emphasis of the R&D professional literature has been on project teams, the purpose of this study is to examine the impact of organization-wide controls on innovativeness at the firm level. In a sample of 57 pharmaceutical firms, this study investigates the influence of organizational controls on the research and development activities of R&D professionals. This study is one of a handful of studies that simultaneously explores the use of input, behavior, and output controls. Two categories of innovation are considered as dependent variables: incremental innovations in the form of drug enhancements and radical innovations in the form of new drugs. Contrary to existing theory and hypotheses developed in this study, the results show that input, behavior, and output control enhanced radical innovation, and input and output controls enhanced incremental innovation. These results challenge several important features of existing models of R&D management and diverge from common beliefs about R&D management at the project level. While it is commonly accepted that incremental and radical innovation should be managed differently, the results of this study suggest otherwise. In this instance, the management of R&D activities may be considered more similar than previously thought.